Exploring Surgical Approaches to Gallbladder Disorders: Efficacy and Outcomes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This paper details the present surgical strategy for gallbladder illness in a Baghdad private hospital. We recorded complications in a group of individuals who had laparoscopic cholecystectomy as opposed to open surgery. Our methodology included looking at cholecystectomies that were done by surgeons after the introduction of laparoscopic surgery. We compared laparoscopic cholecystectomies (LCs) performed between 2016 and 2017 with open cholecystectomies (OCs) performed at the same time by randomly selecting patients. In terms of patient demographics, the LC and OC groups showed no significant differences. More over half, or 43%, of the 63 patients who opted for elective surgery were OC recipients. There was a 4% conversion rate, a 4.8-day average hospital stay, and a 5% readmission rate. All groups had comparable complications. Results: Complications from LCs were similar to those from OCs, even though there were less of them. Even in the elective context, a significant percentage of cholecystectomies remained open during the research period.